Handbook of impact modifiers - Wypych, George (ChemTec Publishing, 2022)
"Handbook of Impact Modifiers provides information on how to modify structure and morphology, improve mechanical performance, and prevent changes during the use of polymeric products by proper selection of impact modifiers. Handbook of Impact Modifiers brings analyses of important publications found in open and patent literature. Special attention is given to the last five years' findings, which brought many new essential developments."--